2022
DOI: 10.1155/2022/4041612
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Tai Chi Training in Cardiorespiratory Fitness of Elderly People

Abstract: Objectives. The purpose of this study was to investigate the influence of Tai Chi on cardiorespiratory fitness (CRF) in elderly people using meta-analysis. Methods. This study used seven electronic databases and data retrieved from randomized controlled trials (RCTs) investigating the role of Tai Chi on CRF in the elderly. All these 24 RCTs were screened and selected from 7 literature databases. The Stata 11.2 software (StataCorp, USA) was used for the meta-analysis, subgroup analysis, and bias test, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…In addition to the above methods, TCM also includes T ai‐Chi, Qi‐gong, yoga , and other methods. 123 These oriental medical strategies have unexpected effects on many diseases, such as cardiorespiratory fitness, 124 rehabilitation after COVID‐19 , 125 cancer, 126 , 127 neurocognitive functions, 128 Stroke 129 and so on.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above methods, TCM also includes T ai‐Chi, Qi‐gong, yoga , and other methods. 123 These oriental medical strategies have unexpected effects on many diseases, such as cardiorespiratory fitness, 124 rehabilitation after COVID‐19 , 125 cancer, 126 , 127 neurocognitive functions, 128 Stroke 129 and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Increased flexibility is closely related to soft tissues, such as ligaments, tendons, muscles, and bone structure (Xinzheng, Fanyuan, & Xiaodong, 2022). The increase in muscle flexibility is also related to the extensibility of the musculotendinous (Tan et al, 2022). Muscle flexibility plays an important role for all age levels, considering that the older a person gets, the less flexibility they have as a result of decreased muscle elasticity and increased joint stiffness in activities (Tang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As the study protocol reported [14], AECOPD patients of clinical-grade severity of I-II [1,15] with a syndrome of heat-phlegm and sthenic-fu, in the age range from 40 to 80 years, who volunteered to participate in the study and signed the informed consent were included in this trial. Meanwhile, patients who met any of the following criteria were excluded: (1) patients complicated with asthma, pneumonia, bronchiectasis, cystic fibrosis, pulmonary tuberculosis, lung cancer, or any other airflow-limiting disease with known causes and characteristic pathology; (2) patients complicated with coronary heart disease, hypertensive heart disease, or heart valve disease; (3) patients needing invasive mechanical ventilation; (4) patients with clinically confirmed or highly suspected pulmonary embolism; (5) patients with severe diseases of cardiovascular, cerebrovascular, hepatorenal, haematopoietic, or endocrine system; (6) patients with intestinal obstruction requiring surgical intervention; (7) pregnant or lactating patients; (8) mentally handicapped patients; (9) patients with alanine aminotransferase (ALT) and aspartate aminotransferase (AST) >1.5 times the upper limit of normal reference or serum creatinine (Scr) above the upper limit of normal reference; (10) patients requiring immunosuppressants; (11) patients taking oral or intravenous antibiotics before screening for more than 3 days in the last 3 months; (12) patients allergic to the basic therapeutic drugs, Chinese herbal medicinal ingredient prescription, or other substances prescribed through the research; (14) patients who have participated in or are participating in other clinical trials in the last 3 months; and (15) patients who were considered inappropriate to participate in this clinical trial by the investigator.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Complementary treatment, whose efficacy was confirmed by many studies, has been widely used in many chronic diseases as an alternative therapy to conventional medicines [8][9][10][11]. Traditional Chinese medicine (TCM), characterised by the theory of syndrome differentiation and overall conditioning, implies its potential advantages in the treatment of COPD.…”
Section: Introductionmentioning
confidence: 99%